A STUDY OF SEMANTIC AND SYNTACTIC FEATURES OF CONDITIONAL SENTENCES IN ENGLISH AND VIETNAMESE LOVE SONGS - Lê Thị Hiệp; Ho Vu Khue Ngoc huong dan (2014)
Introduction; Literature review and theoretical background; Research design and Methodology; ...
Keywords: Lê Thị Hiệp,A STUDY OF SEMANTIC AND SYNTACTIC FEATURES OF CONDITIONAL SENTENCES IN ENGLISH AND VIETNAMESE LOVE SONGS , SEMANTIC, SYNTACTIC , LOVE SONGS